2001
DOI: 10.1128/jb.183.16.4796-4805.2001
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Mutagenesis by Allelic Exchange of choE , Encoding a Cholesterol Oxidase from the Intracellular Pathogen Rhodococcus equi

Abstract: The virulence mechanisms of the facultative intracellular parasite Rhodococcus equi remain largely unknown. Among the candidate virulence factors of this pathogenic actinomycete is a secreted cholesterol oxidase, a putative membrane-damaging toxin. We identified and characterized the gene encoding this enzyme, the choE monocistron. Its protein product, ChoE, is homologous to other secreted cholesterol oxidases identified in Brevibacterium sterolicum and Streptomyces spp. ChoE also exhibits significant similari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 46 publications
2
96
0
2
Order By: Relevance
“…Actual cholesterol oxidase is a bacterial flavoenzyme that is implicated in the ability of bacteria to induce cellular lysis upon infection of their hosts and to induce thrombus (23). Sequence similarity studies have failed to identify a mammalian counterpart, and cholesterol oxidase is generally regarded as unique to bacteria (24).…”
Section: Introductionmentioning
confidence: 99%
“…Actual cholesterol oxidase is a bacterial flavoenzyme that is implicated in the ability of bacteria to induce cellular lysis upon infection of their hosts and to induce thrombus (23). Sequence similarity studies have failed to identify a mammalian counterpart, and cholesterol oxidase is generally regarded as unique to bacteria (24).…”
Section: Introductionmentioning
confidence: 99%
“…CHOx can be an interesting pharmaceutical target for treating bacterial infections. In vitro data suggested that during R. equi infection of the host cell, membrane lysis is facilitated by the induction of extracellular CHOx along with other candidate virulence factors [13]. The membranedamaging activity of R. equi requires the presence of bacterial sphingomyelinase C, thus indicating that the CHOx substrate is not directly accessible to the enzyme in intact membranes [99].…”
Section: Chox As a Potential New Antimicrobial Drug Targetmentioning
confidence: 99%
“…In most of microorganisms, the CHOx is employed in the initial step of cholesterol metabolism. While in case of pathogenic bacteria CHOx acts as membrane-damaging factors and therefore contributes as a virulence factor in the pathogenicity of these bacteria [5,13]. In addition, Streptomyces natalensis produces a cholesterol oxidase (PimE) which acts as a signaling protein for the biosynthesis of an antifungal antibiotic, polyene macrolide pimaricin [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This highly efficient system was used to isolate an attenuated mutant of R. equi, underscoring the usefulness of transposon mutagenesis [4]. Navas et al [50] developed a highly efficient system based on homologous recombination to disrupt the choE gene encoding cholesterol oxidase of R. equi. The development of random and site directed mutagenesis procedures for R. equi was a major development which will facilitate a detailed analysis of R. equi virulence.…”
Section: Development Of Genetic Toolsmentioning
confidence: 99%